MULTIMEDIA AND ANIMATION CREATIVE CONTENT SERIES 1 (Penerbit UTHM, 2026)
Multimedia and animation creative content, presents a collection of innovative studies and creative practices in multimedia and animation. It highlights the integration of artistic creativity with digital technology, emphasizing visual storytelling, design thinking, and interactive media. The chapters explore key areas such as 2D and 3D animation, visual effects, digital illustration, motion graphics, and multimedia development, offering insights into production workflows and current industry trends. Designed as both an academic reference and a source of inspiration, this book encourages students, educators, and practitioners to foster creativity, critical thinking, and collaboration in advancing the future of the creative digital industry.